Making Play or Playing the Game? On the Question of a “Cleft Habitus” at the Doorway to the Art Field - Flisbäck, Marita (Qualitative Sociology Review, 2014)
This article concerns the question of how marginalized individuals at the doorway to the art field manage their position of uncertainty, what Bourdieu calls a “cleft habitus,” and in some cases challenge the repressive norms. Bourdieu’s perspective on how historical crisis prompts change at the macro level is used to view how “micro crises” in the lives of individuals leads to resistance against normative requirements. The article suggests that within situations of micro crises individuals assume three strategies to handle the contradictions they are faced with: 1) expand upon their cultural capital (these resources can then be used in opposition to the institution of the field within which they were accumulated in the first place); 2) move to an alternative scene and audience; or 3) create a new or emergent future horizon through which they can reinterpret their past and present situation.